Performance of the low rank matrix technique in image de-noising - kollamudi, pavani; K Linga Murthy, M.; Mahammed Rafi, G. (International Journal of Engineering and Technology, 2018)
Generally, the technique of low rank matrix (LRM) estimation is a very handy tool in signal processing. The same can be further extended to two dimensional problems in image processing. The tool also emerged as a favourable method to provide solutions through the machine learning and other statistical techniques. In this paper, an attempt is made to employ the LRM to denoise the image which is subjected to guassian noise of certain variance. The performance analysis has been made in terms of calculated peak signal to noise ratio (PSNR).